(3GdCUhd aj GdgfOSIs - (3GbdjOSs
(3ChdgG (B:s
(3GdfbWYI gi TF dGLRA dg , hGdNW gh Whd HdG YQV s
(3BNQgG (B:s
(3abO JHjf Cfg dGjecf Cf jYed ai cQI Tcd ZjQ gPg GdCTcGd GdNeSI hPdc CQOfG Cf fHjf s
(3HgG CTcGd gfOSjI cKjQIs
(3eUOQ GbJfGA GdCUd (B:s
(3GdRjOGfjI ef GdNRGfI GdedcjI HeOjfI GdQHGW (B(1101) s
Keywords: (3GdQjGVjGJs